Surface immunoglobulin on activated human peripheral blood thymus-derived cells. - T L Whiteside; B S Rabin (The Journal of Clinical Investigation, 1976)
Human peripheral blood lymphocytes grown in vitro were stimulated with nonspecific mitogens and in mixed lymphocyte culture. The presence of IgM and thymus (T) surface markers on large and small lymphocytes was investigated by immunofluorescence and correlated with spontaneous rosette formation. All stimulated large lymphocytes formed spontaneous rosettes and all except pokeweed mitogen (PWM)-stimulated large lymphocytes had IgM and T markers. IgG, IgA, and light chain determinants were only detected on PWM-induced large lymphocytes. Thus, surface markers expressed on activated human lymphocytes may differ for different mitogens. IgM was always present on large cells which had the T markers, and it cannot be used to identify a lymphocyte as a bone marrow-derived (B) cell. Due to the overlap of surface markers, the classification into B and thymus-derived (T) cells ought to be restricted to functional phenomena of antibody-production or cell-mediated immunity. Images